Short-term health system responses to epidemics across hard to reach areas in sub-Saharan Africa: A scoping review protocol - Murunga, Annette A.; Ngoye, Ben; Wafula, Francis P.; Kokwaro, Gilbert O. (PloS one, 2024)
Epidemics and Pandemics (disease outbreaks) are the occurrence of cases of disease in excess of what would be normally expected. Epidemic-prone diseases, including emerging and re-emerging diseases, constitute the greatest threat to public health security and disruption of social and economic development. When outbreaks are diagnosed in specific areas, an outbreak response is triggered to stop the spread rapidly. In the past 20 years, the sub-Saharan region has witnessed a marked increase in the number of outbreaks in pandemics, such as cholera, dengue, A/H5N 1 influenza among others. While efforts toward containment have been individually studied, we have no recent studies that examine them collectively in order to draw appropriate comparisons, no recent studies that have especially focused on hard-to-reach areas, and none that have applied a health systems lens. This study thus details a scoping review of short-term health system responses to epidemics across hard-to-reach areas in sub-Saharan Africa. The scoping review will be undertaken following PRISMA guidelines. A modified Donabedian framework will be used to understand the different approaches used while responding to epidemics. The review will focus on published and unpublished studies that report short-term health systems responses to epidemics in hard to reach areas. These will be gleaned from PubMed, google scholar and Cochrane, supplemented by a Google advanced search. In addition, manual searches will be carried out through related articles and websites. Data will be charted, coded, and narratively synthesized. our exclusion criteria will include; protocols, book chapters and countries not identified as hard to reach areas in SSA. We anticipate developing a document that will show the different approaches health systems in different countries used when responding to epidemics. The information generated will contribute to strengthening future epidemic responses by identifying best practices and innovative ideas as well as highlighting knowledge gaps.